Effects of mulligan concept in classical ballet dancers with pain in the lower limbs - Aguiar, Letícia Lopes; dos Santos Araújo, Vanessa Assunção; de Andrade Mesquita, Laiana Sepúlveda (Manual Therapy, Posturology & Rehabilitation Journal, 2020)
Introduction: The Mulligan concept is a manual therapy technique that addresses the restoration of arthrocinematic processes and inadequate osteocinematic movements, resulting in reduced muscle tension, postural failure and pain relief. Objectives: To analyze the effectiveness of the Mulligan concept in reducing lower limb pain processes in classical dancers. Methods: Longitudinal study, approved by the Ethics and Research Committee of the Universidade Estadual do Piauí, according to the decision of No. 2064503, composed by 4 classical dancers. An evaluation of the pain level was performed using a digital algometer (Wagner Instruments) with a ten-kilogram-force (Kgf) capacity in dancers who presented painful symptoms in the knee. The level pain before and after the intervention with the Mulligan concept was verified in the following points: patellar ligament (PL), medial collateral ligament (MCL) and lateral collateral ligament (LCL). The Mulligan concept was performed actively, painlessly, with adjustments by the therapist and was maintained at the end of the knee amplitude for 10 seconds. This protocol was repeated 3 times in the first attendance, in the second 10 times, in the third there were 2 repetitions of 10 slides and in the subsequent attendances there were 3 repetitions of 10 slides. Results: An increase in the average of the pain threshold in patellar, medial collateral and lateral collateral ligaments was observed in all participants of the study, when comparing the initial values of the 1st care and the final values of the 12th Mulligan session. The lateral collateral ligament presented the most significant result, with p = 0.02. Statistical analysis was performed through the BioEstat 5.0 program. The Shapiro-Wilk tests were applied to assess the normality of variables, and the t-student test was considered statistically significant p<0.05. Conclusion: statistically the lateral collateral ligament showed an immediate and lasting significant improvement in the pain threshold of the dancers with the therapeutic intervention of the Mulligan concept.